A Maintenance Strategy for Dosing Pumps Using Reliability-Centered Maintenance (RCM) and Spare Parts Ordering to Improve the Reliability of the Clean Water Supply System at PT. Dain Celicani Cemerlang - Johannes Kevin Purba; Aulia Ishak; Nurhayati Nurhayati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The continuity of the clean water distribution process at PT Dain Celicani Cemerlang is highly dependent on the reliability of the dosing pumps. However, the maintenance system currently in place is still reactive (corrective maintenance), resulting in high operational downtime and uncontrolled maintenance costs. This study aims to improve the reliability of the clean water supply system by designing a maintenance strategy based on Reliability-Centered Maintenance (RCM) and optimizing spare parts management through a spare parts ordering system. The research method used is descriptive quantitative analysis, which involves analyzing reliability parameters such as Mean Time Between Failures (MTBF), Mean Time To Repair (MTTR), and Risk Priority Number (RPN) through a Failure Mode and Effect Analysis (FMEA) approach. In addition, the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods were used to determine the most efficient spare parts ordering policy. The research results show that the implementation of appropriate RCM strategies (such as preventive maintenance and scheduled replacement) can significantly reduce system downtime by 89.21% and increase machine availability from 96.73% to 99.65%. From a cost perspective, implementing RCM yields savings of 24.27%, while integrating the EOQ and POQ methods into spare parts management reduces inventory costs by up to 41.73% compared to the company’s current system. In conclusion, the integration of RCM with a structured spare parts ordering system is highly effective in ensuring the company’s operational stability and cost efficiency.